Menemukan Universalitas Pesan Alquran Sebagai Keniscayaan dalam Penafsiran Multi-Interdisipliner - wardani, wardani; Nadhiroh, Wardatun (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2018)
This article aims to lay a philosophical foundation on the universality of the message of the Qurâ€™an as a necessity in a multi-interdisciplinary approach to interpreting the Qurâ€™an. The study departs from the thoughts of Qurâ€™anic scholars from the classical to the contemporary period as set out in their works. The â€œuniversalityâ€ here means two senses: first, compatibility of the message, owing to its universal and perennial ethical contents, to be applied across boundaries of time and space; second, various aspects of contents of the Qurâ€™an, such as theological, legal, ethical, and scientific issues. This article also suggests methods in exploring the universality of the Qurâ€™anic doctrines and gives one example of its application, especially in understanding Quranic values in its doctrine of warfare. The authors conclude that an integrative approach to the Qurâ€™an is needed to be accompanied by an awareness of the universality of the message of the Qurâ€™an which lies in the spirit of ethical principles and the need for meaning in a broader spectrum in the modern era. Neglecting its universal message will cause interpretations to lose this spirit, such as classical Moslem interpretersâ€™ understanding on jihad-verses by insisting that the jihad as warfare is a permanent obligation upon Moslems. The falsehood of the interpretation is due to neglecting the ethical principle i.e. humanity behind the law of reciprocity that underlies particular verses on warfare.